Measurementof aerodynamiccharacteristics fluxes near thesurface of the body - Исaтaев, М.С.; Молдaбековa, Д.; Омaрaлинa, A.; Есенaлиевa, A.; Сейдуллa, Ж.К. (Recent Contributions to Physics, 2016)
Research of aerodynamics of bluff bodies in the flow of liquids and gases is one of the major issues of industrial aerodynamics. Theseproblems can be attributed to the study of cross-flow constrained the flow of a circular cylinder. The objectives of this work investigation of the effect of the Reynolds number on the flow patterns in the aft area of the cylinder. The studies were conducted in the range of numbers 2<Re<2·105 and 0,7<Pr<550. Experiments have shown that a significant impact on the aerodynamics of the flow around a circularcylinder has a degree of blockage. This changes not only the quantitative characteristics, but there are a number of qualitative changes in the flowregime. For example, set two kinds of flow in the wake of the body: thefirst is characterized by the existence of periodic vortex shedding at q = 0,385 and 104<Re<2·105 second - the lack of periodicity, ie, the presence of chaotic vortex flows at q = 0,629. When changing flow in the wake of the periodic to aperiodic length averaged circulation flowzone varies from l / d = 1,5 to 3,0.